"Communities Change When Individuals Change": The sustainability of system‐challenging collective action. (28th April 2021) - Rao, Neomi; Power, Séamus A.
Abstract: People who challenge the status quo through collective action face tremendous obstacles—not just practically, but in their ways of thinking, existing, and relating to others. This article addresses how collective actors sustain their engagement in the face of such high costs. System‐challenging collective actors must reimagine and enact new, non‐normative ways of thinking, existing, and relating that transform the status quo. This article explores the social psychological processes underlying sustained system‐challenging collective action through activists' narratives of politicization, experiences of identity change, and reimagination of social structures. We draw on contributions from social psychological theories of system justification and social identity to examine how system‐challenging collective action is motivated and sustained. Through interviews with Chicago‐based activists and organizers engaged in system‐challenging collective action, we implement a qualitative thematic analysis to propose that sustainability arises from three integrated factors: shared identity, system‐challenging ideology, and intentional community.